EVALUATION OF MALONDIALDEHYDE AND SUPEROXIDE DISMUTASE IN PATIENTS OF ALCOHOLIC LIVER DISEASE AND HEALTHY CONTROLS: A CROSS-SECTIONAL STUDY - Kumar, Ranjeet; Gurupadappa. K; Mishra, Prakash Chandra (Student's Journal of Health Research Africa, 2024)
Background Oxidative stress and an imbalance between oxidants and antioxidants are hallmarks of alcoholic liver disease (ALD), a major global cause of morbidity and mortality. Superoxide dismutase (SOD) and malondialdehyde (MDA) are important indicators for assessing the antioxidant and oxidative stress state in ALD. To comprehend the function of oxidative stress in ALD, this study intends to assess the blood levels of MDA and SOD in patients with ALD and compare them with healthy controls. Methods An analytical cross-sectional study was conducted involving 120 male participants. Serum MDA and SOD levels were measured using the Draper and Hadley method and the Marklund and Marklund method, respectively. Statistical analysis was done using an unpaired t-test with a significance level set at p < 0.05. Results The study included 120 male participants, divided into two groups: 60 patients with ALD and 60 healthy controls. All participants were age- and sex-matched. The serum MDA levels were notably higher in ALD patients (mean ± SD: 11.45 ± 3.01 nmol/ml) compared to controls (mean ± SD: 3.86 ± 0.73 nmol/ml) (p < 0.001). Similarly, serum SOD levels were notably elevated in ALD patients (mean ± SD: 13.69 ± 1.07 units/ml) compared to controls (mean ± SD: 5.04 ± 1.46 units/ml) (p < 0.001). A strong positive correlation was detected between MDA and SOD levels (rs = 0.988, p < 0.001). Conclusion ALD patients exhibit enhanced oxidative stress as indicated by elevated serum MDA levels and a concomitant rise in antioxidant SOD levels. This suggests a compensatory mechanism against oxidative damage in ALD. Recommendations Future studies should focus on therapeutic interventions aimed at modulating oxidative stress and antioxidant defense mechanisms in ALD.